The use of an endovascular balloon to increase the safety of laparoscopic decompression of the abdominal trunk - Z. M. Khamid; A. K. Bazunov; A. V. Biryukov; D. I. Vasilevsky; A. Yu. Korolkov; S. G. Balandov; S. Yu. Puzanov; I. P. Rumyantsev; S. F. Bagnenko (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to increase the safety of laparoscopic decompression of the abdominal trunk.METHODS AND MATERIALS. The results of treatment of 30 patients who underwent laparoscopic decompression of the celiac trunk were analyzed. Intraoperative bleeding requiring conversion to laparotomy occurred in two (6.7%) cases.RESULTS. To prevent such a complication, a method of preventive installation of a balloon catheter into the celiac trunk was introduced, which allows creating a temporary occlusion of the vessel in case of damage. A similar approach was used in 10 (33.3%) patients. The need to cover the lumen of the vessel with a balloon arose in one observation (3.3% of all patients and 10.0% using this technique). Bleeding from the inferior phrenic artery, which originated from the celiac trunk, was stopped by laparoscopic access.CONCLUSION. The experience presented in this paper allows us to consider the installation of a balloon boat in the celiac trunk as one of the possible ways to improve the safety of its laparoscopic decompression. Further research is needed to obtain a definitive picture of the effectiveness of this approach.